PENGARUH BALANCE SCORECARD TERHADAP KINERJA PERGURUAN TINGGI - Nisak, Nuril Ainun; Yuniarti, Rina (National Conference on Applied Business, Education, & Technology (NCABET), 2024)
This study aims to examine the effect of Balanced Scorecard (BSC) on university performance with a focus on Muhammadiyah Aisyiyah Universities (PTMA) in Sumatra. This study involved 36 universities as a population and used a saturated sample method by involving 36 universities as research samples. Research data were obtained through questionnaires distributed to the Rector / Vice Rector / Head of the Quality Assurance Agency online and offline. The data analysis technique used was simple linear regression analysis using SPSS software version 22. The results showed that the application of BSC had a positive and significant effect on university performance in PTMA. These results indicate that BSC can be used to improve college performance